PELAKSANAAN PENYELIDIKAN TINDAK PIDANA PEMILU TAHUN 2019 OLEH KEPOLISIAN SELAKU PENEGAK HUKUM TERPADU (GAKKUMDU) DI SUMATERA BARAT - Joni Saputra dan Nurlinda Yenti (Normative Jurnal Ilmiah Hukum, 2021)
An integrated law enforcement center, or called Sentra Gakkumdu, is an effort to equalize understanding and patterns of handling election crimes among the Election Supervisory Body of the Republic of Indonesia, the National Police of the Republic of Indonesia and the Attorney General's Office of the Republic of Indonesia. Sentra Gakkumdu is regulated in Article 486 paragraph (1) of Law Number 07 of 2017 concerning General Elections to become a Law which states in paragraph (1): "To equate the understanding and pattern of Election Crime Handling, Bawaslu, the Indonesian National Police, and the Attorney General's Office of the Republic of Indonesia established Gakkumdu. â€With clear regulations regarding the authority in handling election criminal cases, the Integrated Law Enforcement Center as the party carrying out the prosecution of violations is required to process any suspected election criminal acts. Such as the case that occurred in Dharmasraya Regency on September 27 2018, where there was a declaration of support from Wali Nagari in Dharmasraya Regency for Jokowi which was carried out at the office of Wali Nagari Sungai Dareh. This was said by the Chairman of the General Election Supervisory Agency of West Sumatra Province "Article 1 number 35 of the Election Law: Election Campaign is the activity of election participants or other parties appointed by election participants to convince voters by offering a vision, mission, program and / or image. Election Contestants